2012
DOI: 10.1007/s00395-012-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

Secretome of apoptotic peripheral blood cells (APOSEC) attenuates microvascular obstruction in a porcine closed chest reperfused acute myocardial infarction model: role of platelet aggregation and vasodilation

Abstract: Although epicardial blood flow can be restored by an early intervention in most cases, a lack of adequate reperfusion at the microvascular level is often a limiting prognostic factor of acute myocardial infarction (AMI). Our group has recently found that paracrine factors secreted from apoptotic peripheral blood mononuclear cells (APOSEC) attenuate the extent of myocardial injury. The aim of this study was to determine the influence of APOSEC on microvascular obstruction (MVO) in a porcine AMI model. A single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 64 publications
0
43
0
Order By: Relevance
“…Both methods revealed improved microvascular blood flow in treated animals. In addition, apoptotic PBMC-S induced up-regulation of eNOS, iNOS in cultured H UVECs, and vasodilator-stimulated phosphoprotein (VASP) activation in platelets [99]. These data indicate that apoptotic PBMC-S not only caused direct cytoprotective effects in injured hearts, but also induced systemic effects on circulating platelets and endothelial cells.…”
Section: Apoptosis and The Rise Of The Phoenix Signaling Pathwaymentioning
confidence: 70%
“…Both methods revealed improved microvascular blood flow in treated animals. In addition, apoptotic PBMC-S induced up-regulation of eNOS, iNOS in cultured H UVECs, and vasodilator-stimulated phosphoprotein (VASP) activation in platelets [99]. These data indicate that apoptotic PBMC-S not only caused direct cytoprotective effects in injured hearts, but also induced systemic effects on circulating platelets and endothelial cells.…”
Section: Apoptosis and The Rise Of The Phoenix Signaling Pathwaymentioning
confidence: 70%
“…ApoSec was able to induce angiogenesis not only in aortic rings, but also in spinal cord tissue ex-vivo, which was confirmed immunohistologically using confocal microscopy [31] . Aside from neovascularization, previously described inhibition of micro-vascular obstruction via inhibition of thrombocyte activation and vasodilation might also be involved in observed improved vascularity in treated animals [24,31] . To assess possible involved immunologic mechanisms further investigation revealed higher levels of CD68 expression with concomitant lower expression levels of inducible NO-synthase (iNOS) 3 days after injury in animals treated with ApoSec.…”
Section: Research Highlightmentioning
confidence: 90%
“…Subsequent centrifugation allowed further processing of the cell-free supernatant or secretome, also referred to as conditioned medium. Several pre-clinical models were used to investigate the therapeutic potential of this secretome derived from apoptotic PBMCs (ApoSec, patent number: WO2010/070105, WO2010/079086) [22][23][24][25][26][27][28] . Therapeutic efficacy was shown to be a synergistic effect caused by modulation of multiple molecular pathways, many of which are also known to be involved in secondary cascades after SCI.…”
Section: Research Highlightmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoetzenecker et al showed that, in addition to an effect on intracellular myocardial signaling cascades, apoptotic PBMC-S preserved porcine epi/myocardial microvascular perfusion in a closed chest reperfusion infarction model [99]. Microvascular obstruction was measured by functional magnetic resonance imaging (fMRI) and cardiac catheterization in treated animals.…”
Section: Paradigm Changes In Tissue Repair—validation Of the Pbmc Secmentioning
confidence: 99%